Co-parasitism by chigger mites (Trombidiformes: Leeuwenhoekiidae) and soft ticks (Ixodida: Argasidae) in Brazilian anurans, with the description of a new Hannemania species - Isabella Pereira Pesenato; Ricardo Bassini-Silva; Pedro Paulo Goulart Taucci; Nadya Carolina Pupin; Murillo Castelo Branco Monho; Giovanna Rafaeli Rezende; Maria Eduarda Barbosa de Souza-Silva; Sebastian Muñoz-Leal; Marcelo B. Labruna; Darci Moraes Barros-Battesti; Fernando de Castro Jacinavicius (Systematic Parasitology, 2026)
Bokermannohyla frogs comprise species distributed across different Brazilian biomes, several of which are currently listed as endangered species. These anurans host a diversity of parasites that may negatively affect their survival. Several tick species of the family Argasidae and chigger mites of the family Leeuwenhoekiidae exhibit host specificity toward this group. Here, we report a case of co-parasitism by argasid ticks and chigger mites in this frog genus collected in the Bahia State, Brazil, and describe a new species of Hannemania, H. diamantinensis sp. nov. Anurans were captured in Chapada Diamantina National Park, and ectoparasites were collected and identified using morphological methods. Ticks were identified as Ornithodoros saraivai , while chigger mites correspond to a new species. This represents the first record of O. saraivai in Bahia State, and the description of a new Hannemania species increases the number of Brazilian known species to eight.

Quantitative assessment of ticks in a hot cave in the Amazon reveals that the genus Antricola (Ixodida: Argasidae) has the highest cave tick population density on planet - Flávio A. Terassini; Marcelo B. Labruna; Sebastián Muñoz-Leal; Luís Marcelo A. Camargo; André de A. R. Aguirre (Experimental and Applied Acarology, 2026)
Within Argasidae ticks, the genus Antricola is restricted to the New World and exhibits a unique biology: only larvae are hematophagous and parasitize bats, whereas nymphs and adults are free-living and supposedly to feed on bat guano in hot caves with high temperatures (30–38 °C) and relative humidity close to 100%. This study quantified the tick population in an Amazonian hot cave located in the Natural Park of Porto Velho (Rondônia, Brazil), inhabited by thousands of insectivorous bats. Standardized guano samples (100 cm² at 10 points) were collected during dry and rainy seasons and examined in the laboratory. The guano-covered area totaled 146.34 m². A total of 7,388 ticks was collected in the dry season and 8,753 in the rainy season, with more than 99% belonging to Antricola , mainly A. delacruzi . The estimated mean density was 80,705 ticks/m², corresponding to an approximate population of 11.8 million individuals on the cave floor—the highest tick density ever recorded in a cave worldwide. Only nymphs and adults were found, suggesting that Antricola eggs and larvae remain in wall crevices, and that rapid larval development, combined with continuous guano feeding, promotes long post-larval longevity. These findings highlight a highly specialized host–parasite dynamic and emphasize the importance of conserving Amazonian cave ecosystems and surrounding forests, which are threatened by deforestation and other anthropogenic pressures.

Transstadial and transovarial perpetuations of Borrelia venezuelensis in Ornithodoros rudis, with demonstration of vector competence - Felipe R. Jorge; Glauber M. B. de Oliveira; Igor S. Silito; Matheus Pasini Martins; Sebastián Muñoz-Leal; Marcelo B. Labruna (Experimental and Applied Acarology, 2026)
Ticks of the genus Ornithodoros are recognized vectors of relapsing fever group Borrelia , such as Borrelia venezuelensis , whose infection dynamics in its vector, Ornithodoros rudis , remains poorly understood in Brazil. This study aimed to investigate the transstadial perpetuation and transovarial transmission of B. venezuelensis in O. rudis and the vector competence of all parasitic stages of this tick species. Experimental colonies were maintained under controlled laboratory conditions, and ticks were fed on Syrian hamsters ( Mesocricetus auratus ). Infection in hamsters was monitored using dark field microscopy and real-time PCR. Borrelia venezuelensis was detected across multiple tick life stages, and its presence in larvae derived from infected females confirmed transovarial transmission. Vector competence for B. venezuelensis was demonstrated for larvae, nymphs and adults of O. rudis. Additionally, neurological symptoms and sudden death were observed in some hamsters, possibly associated with toxicosis due to heavy tick infestation. These findings provide the first experimental evidence of transstadial and transovarial maintenance of B. venezuelensis in O. rudis , reinforcing its role as a competent vector and contributing to a better understanding of the eco-epidemiology of relapsing fever in South America.

Assessment of tick populations associated with capybaras in natural reserves and human-modified environments with or without invasive plants in the state of São Paulo, Brazil - Matheus Pasini-Martins; Rubia Diaz Taveiros Kuhne; Carolina Moura de Oliveira; Lina C. Binder; Igor S. Silito; Adriano Pinter; Fernanda B. Passos Nunes; Thiago F. Martins; José Henrique de Hildebrand e Grisi Filho; Wayne Dawson; Philip A. Stephens; Dalva Maria da Silva Matos; et al. (Experimental and Applied Acarology, 2026)
In southeastern Brazil, capybaras ( Hydrochoerus hydrochaeris ) are main hosts of the ticks Amblyomma dubitatum and Amblyomma sculptum ; the latter has great medical importance for being the main vector of Rickettsia rickettsii , the agent of Brazilian spotted fever (BSF). This study aimed to quantify ticks in areas invaded and not invaded by exotic plants ( Hedychium coronarium , Cenchrus purpureus or Megathyrsus maximus ) within capybaras’ living areas in São Paulo state. Tick populations were quantified in 24 capybara habitats, eight in natural reserves and 16 human-modified landscapes; the latter were composed of eight BSF-endemic areas and eight BSF-nonendemic areas. In the 24 areas, ticks were sampled in plots of natural forests and plots with at least one of the three invasive plants. Both presence and density of A. sculptum were higher in human-modified landscapes, while the presence and density of A. dubitatum tended to be similar among human-modified landscapes and natural reserve areas. The two tick species were collected both in areas colonized by invasive plants ( H. coronarium , M. maximus , and/or C. purpureus ) and in areas of non-invaded vegetation. However, a higher density of A. dubitatum was observed in areas of H. coronarium and a lower density of A. sculptum in this type of vegetation. Within human-modified landscapes, there was a higher density of A. sculptum in BSF-endemic areas when compared to non-endemic areas, unlike A. dubitatum , which remained at an almost constant density and presence among BSF-endemic and non-endemic areas. Plant invasions may have some role in the ecology of capybara-associated ticks.

Epidemiological investigation of Coxiella burnetii in farms after an outbreak of Q fever in slaughterhouse workers - Tatiana Evelyn Hayama Ueno; Natalia de Moura Fagundes; Fábio Gregori; Sérgio Santos de Azevedo; Eidi Yoshihara; Luiz Henrique Barrochelo; Marcelo B. Labruna (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

The possibility of the brown dog tick (Rhipicephalus linnaei) dispersing through veterinary facilities in urban areas - Maria Carolina A. Serpa; Jonas Moraes-Filho; Isabella P. Pesenato; Gabrielle R. de Andrade; Thiago F. Martins; Igor S. Silito; Lina C. Binder; Marcos Amaku; Marcelo B. Labruna (Veterinary Parasitology, 2026)

Coxiella burnetii in ruminants from Somalia - Aamir M. Osman; Ahmed A. Hassan-Kadle; Igor S. Silito; Caroline Tostes Secato; Abdalla M. Ibrahim; Maria Carolina A. Serpa; Marcos R. André; Thállitha S. W. J. Vieira; Marcelo B. Labruna; Rosangela Z. Machado; Rafael F. C. Vieira (Tropical Animal Health and Production, 2025)
Q fever in humans and coxiellosis in ruminants are caused by Coxiella burnetii , a zoonotic obligate intracellular bacterium. This infection poses significant health and economic risk. Effective control strategies rely on a thorough understanding of their epidemiology. In this study, we examined the prevalence of C. burnetii in 372 ruminants (190 goats, 133 cattle, and 49 sheep) from the Lower Shabelle and Benadir Regions of Somalia. Diagnostic testing was performed using a quantitative PCR (qPCR) assay that targets the bacterium’s repetitive element IS111 and the Indirect Fluorescent Antibody Test (IFAT) against the C. burnetii strain At12. A total of 47 out of 372 (12.6%) ruminants tested positive for anti- Coxiella burnetii IgG antibodies, with seropositivity detected in 40 out of 190 goats (21.1%) with endpoint titers ranging from 64 to 2,048, and 7 out of 49 sheep (14.3%) with endpoint titers ranging from 64 to 8,192, while all cattle tested negative. Notably, only one goat that was seropositive also tested positive for C. burnetii by qPCR, while all other ruminants were negative. These findings provide evidence of the presence of C. burnetii in Somali livestock, emphasizing its public health risk and highlighting the necessity for targeted surveillance and control strategies to prevent zoonotic transmission.

Seach for tick-borne agents and detection of a novel Ehrlichia sp. in ticks from wild rabbits in Northern Spain - Igor Silva Silito; Matheus Pasini Martins; Thallitha Samih Wischral Jayme Vieira; Maria Carolina A. Serpa; Isabella Pereira Pesenato; Agustin Estrada-Peña; Marcelo B. Labruna (Experimental and Applied Acarology, 2025)

Vector competence and transovarial transmission of Rickettsia rickettsii in Rickettsia bellii-infected and -uninfected Amblyomma dubitatum ticks - Lina C. Binder; Carlos E. C. Fanchini; Herbert S. Soares; Matheus P. Martins; Igor S. Silito; Marcelo B. Labruna (Experimental and Applied Acarology, 2025)

Conspecific hyperparasitism in two Ornithodoros species (Ixodida: Argasidae) endemic to Brazil, and interspecific hyperparasitism between Amblyomma sculptum and Rhipicephalus microplus (Ixodida: Ixodidae) - Thiago F. Martins; Simone M. Simons; Caio Monteiro; Haile D. F. Chagas; Rafael A. Carvalho; Arthur M. Santana; Darci M. Barros-Battesti; Glauber M. B. de Oliveira; Livio M. Costa-Junior; Marcelo B. Labruna; Hermes R. Luz (Experimental and Applied Acarology, 2025)

The Ixodes auritulus complex (Acari: Parasitiformes: Ixodidae) in the Southern Cone of America - José M. Venzal; Evelina L. Tarragona; Fernando S. Flores; María L. Félix; Gabriel L. Cicuttin; Patrick S. Sebastian; Marcelo B. Labruna; Alberto A. Guglielmone; Santiago Nava (Systematic Parasitology, 2025)

Analysis of free-living seabirds from Brazil as potential hosts of Toxoplasma gondii and serological investigation for antibodies against Leptospira spp. - Igor C. L. Acosta; Daniela P. Chiebao; Patricia P. Serafini; Gabriel Canani; Hilda F. J. Pena; Marcos B. Heinemann; Antonio F. Souza-Filho; Cynthia Campolina; Caio A. Marques; Tatiana S. Neves; Marcio A. Efe; Guilherme T. Nunes; et al. (Veterinary Research Communications, 2025)

New records of ticks (Acari: Ixodida) and Rickettsia species in El Salvador - Luis E. Romero; Francis Alvarenga; Lina C. Binder; Maria Carolina A. Serpa; Sebastián Muñoz-Leal; Marcelo B. Labruna (Experimental and Applied Acarology, 2025)

Ticks infesting terrestrial small mammals in a rural settlement in the Amazonas state, Brazil - Juliana Machado Portela; Alessandra Ferreira Dales Nava; Helder Ribeiro Batista; Thiago F. Martins; Sebastian Muñoz-Leal; Maria Nazareth Ferreira da Silva; Salatiel Ribeiro Dias; Marcelo B. Labruna; Antonio Humberto Hamad Minervino (Experimental and Applied Acarology, 2024)

Natural infection of free-ranging capybaras (Hydrochoerus hydrochaeris) with Anaplasmataecea and Rickettsiaceae bacteria in the Iberá wetlands ecoregion, Argentina - Lucas D. Monje; Ayelen T. Eberhardt; Paula J. Vaschalde; Johann Barolin; Francisco B. Costa; Marcelo B. Labruna; Pablo M. Beldomenico (Veterinary Research Communications, 2024)

Rickettsia communities and their relationship with tick species within and around the national park of Iguaçu, Brazil - Amália Regina Mar Barbieri; Adriane Suzin; Lais Miguel Rezende; Matheus Henrique Tognolli; Alexandre Vogliotti; Pablo Henrique Nunes; Graziela Tolesano Pascoli; Vanessa do Nascimento Ramos; Jonny Yokosawa; Maria Carolina de Azevedo Serpa; Samuel Fernando Adami; Marcelo B. Labruna; et al. (Experimental and Applied Acarology, 2023)

Rickettsial infection in ticks from a natural area of Atlantic Forest biome in southern Brazil - Felipe da Silva Krawczak; Lina C. Binder; Caroline Sobotyk; Francisco B. Costa; Fábio Gregori; Thiago F. Martins; Gracielle T. Pádua; Jonas Sponchiado; Geruza L. Melo; Gina Polo; Marcelo B. Labruna (Experimental and Applied Acarology, 2022)

Serosurvey of spotted fever group Rickettsia in equids from western Pará, Amazon, Brazil - Antonio Humberto Hamad Minervino; Emelie Andersson; Emma Norlander; Thiago Rocha Moreira; Solange Maria Gennari; Nohora Mercado Caruso; Jonas Moraes Filho; Arlei Marcili; Thiago Fernandes Martins; Marcelo B. Labruna (Experimental and Applied Acarology, 2022)

New records of soft ticks (Acari: Argasidae) in the Caatinga biome of Brazil, with a phylogenetic analysis of argasids using the nuclear Histone 3 (H3) gene - Felipe R. Jorge; Lorena M. B. de Oliveira; Meylling M. L. Magalhães; Bárbara Weck; Glauber M. B. de Oliveira; Maria Carolina A. Serpa; Francisco B. P. Moura; Romilson S. Lopes Júnior; Jessica M. L. dos Santos; Bruno M. Teixeira; Sebastián Muñoz-Leal; Marcelo B. Labruna (Experimental and Applied Acarology, 2022)

Tick-borne zoonotic agents infecting horses from an urban area in Midwestern Brazil: epidemiological and hematological features - João Bosco Vilela Campos; Filipe Santos Martins; Carina Elisei de Oliveira; Amanda Alves Taveira; João Roberto de Oliveira; Luiz Ricardo Gonçalves; Matheus Dias Cordeiro; Ana Claudia Calchi; Lina de Campos Binder; Maria Carolina de Azevedo Serpa; Amália Regina Mar Barbieri; Marcelo B. Labruna; et al. (Tropical Animal Health and Production, 2021)

Morphological descriptions of the nymph and adults of Ornithodoros clarki, the larva and nymph of Ornithodoros rondoniensis, with notes on their phylogenetic relationships - Marcelo B. Labruna; Santiago Nava; Andrea Rebollo-Hernández; Carmen Guzmán-Cornejo; Ligia V. Hernández; Lillian Domínguez; Sebastián Muñoz-Leal; José M. Venzal (Systematic Parasitology, 2021)

Ticks and tick-borne Rickettsia in El Salvador - Luis Romero; Francisco B. Costa; Marcelo B. Labruna (Experimental and Applied Acarology, 2021)

Maintenance of the infection by Rickettsia amblyommatis in Amblyomma cajennense sensu stricto ticks and evaluation of vector competence - Hector R. Benatti; Lina C. Binder; Francisco B. Costa; Herbert S. Soares; Hermes R. Luz; Marcelo B. Labruna (Experimental and Applied Acarology, 2020)

Host movement and time of year influence tick parasitism in Pantanal birds - Alan Fecchio; Thiago F. Martins; Jeffrey A. Bell; Gabriel M. De LaTorre; Elaine R. Bueno; Moises J. Malaquias; João B. Pinho; Marcelo B. Labruna; Raphael I. Dias (Experimental and Applied Acarology, 2020)

Immature ticks on wild birds and the molecular detection of a novel Rickettsia strain in the Ibitipoca State Park, southeastern Brazil - Diego G. Ramirez; Hermes R. Luz; Sebastián Muñoz-Leal; Walter Flausino; Igor C. L. Acosta; Thiago F. Martins; Maristela Peckle; Helio F. Santos; Guilherme P. Furusawa; Marcelo B. Labruna; João L. H. Faccini (Experimental and Applied Acarology, 2020)

Ornithodoros capensis sensu stricto (Ixodida: Argasidae) in Coiba National Park: first report for Panama, with notes on the O. capensis group in Panamanian shores and Costa Rica - Sebastián Muñoz-Leal; Lillian Domínguez; Brittany A. Armstrong; Marcelo B. Labruna; Sergio Bermúdez C (Experimental and Applied Acarology, 2020)

Redescription of the larva, and description of the nymphal and adult stages of Ornithodoros peruvianus Kohls, Clifford & Jones, 1969 (Acari: Argasidae) - Sebastián Muñoz-Leal; Daniel González-Acuña; Marcelo B. Labruna; José M. Venzal (Systematic Parasitology, 2020)

Borrelia burgdorferi sensu lato infecting Ixodes auritulus ticks in Uruguay - Luis A. Carvalho; Leticia Maya; María T. Armua-Fernandez; María L. Félix; Valentin Bazzano; Amalia M. Barbieri; Enrique M. González; Paula Lado; Rodney Colina; Pablo Díaz; Marcelo B. Labruna; Santiago Nava; et al. (Experimental and Applied Acarology, 2020)

A third species of Nothoaspis Keirans & Clifford, 1975 (Acari: Argasidae): Nothoaspis setosus (Kohls, Clifford & Jones, 1969) n. comb - Sebastián Muñoz-Leal; Flavio A. Terassini; Arlei Marcili; Glauber M. B. Oliveira; Luís Marcelo A. Camargo; Marcelo B. Labruna (Systematic Parasitology, 2019)

Serologic and molecular survey of Rickettsia spp. in dogs, horses and ticks from the Atlantic rainforest of the state of Bahia, Brazil - Philipe B. de Oliveira; Tatiani V. Harvey; Hllytchaikra F. Fehlberg; Josiane M. Rocha; Thiago F. Martins; Igor C. L. da Acosta; Marcelo B. Labruna; João L. H. Faccini; George R. Albuquerque (Experimental and Applied Acarology, 2019)

A relapsing fever Borrelia and spotted fever Rickettsia in ticks from an Andean valley, central Chile - Sebastián Muñoz-Leal; Arlei Marcili; Danny Fuentes-Castillo; Mauricio Ayala; Marcelo B. Labruna (Experimental and Applied Acarology, 2019)

A high gene flow in populations of Amblyomma ovale ticks found in distinct fragments of Brazilian Atlantic rainforest - Gislene F. S. R. Fournier; Adriano Pinter; Renata Santiago; Sebastian Muñoz-Leal; Thiago Fernandes Martins; Marcos Gomes Lopes; Karen D. McCoy; Celine Toty; Mauricio C. Horta; Marcelo B. Labruna; Ricardo A. Dias (Experimental and Applied Acarology, 2019)

Detection of Rickettsia spp. in ticks associated to wild mammals in Northeastern Brazil, with notes on an undetermined Ornithodoros sp. collected from marsupials - Maerle O. Maia; Valdinei C. Koppe; Sebastián Muñoz-Leal; Thiago F. Martins; Arlei Marcili; Marcelo B. Labruna; Richard Campos Pacheco (Experimental and Applied Acarology, 2018)

A morphological and phylogenetic analysis of Ornithodoros marinkellei (Acari: Argasidae), with additional notes on habitat and host usage - José M. Venzal; Santiago Nava; Ligia V. Hernández; Jorge Miranda; Arlei Marcili; Marcelo B. Labruna (Experimental and Applied Acarology, 2018)

Detection of Rickettsia spp. in ticks parasitizing toads (Rhinella marina) in the northern Brazilian Amazon - Hermes Ribeiro Luz; Ercileide Silva-Santos; Carlos Eduardo Costa-Campos; Igor Acosta; Thiago F. Martins; Sebástian Muñoz-Leal; Douglas McIntosh; João Luis Horacio Faccini; Marcelo B. Labruna (Experimental and Applied Acarology, 2018)

Ticks (Acari: Ixodidae) of the state of Amazonas, Brazil - Sergio L. Gianizella; Thiago F. Martins; Valeria C. Onofrio; Nair O. Aguiar; Waleska Gravena; Carlos A. R. do Nascimento; Laérzio C. Neto; Diogo L. Faria; Natália A. S. Lima; Monica R. Solorio; Louise Maranhão; Ivan J. Lima; et al. (Experimental and Applied Acarology, 2018)

Life-cycle of Amblyomma oblongoguttatum (Acari: Ixodidae) under laboratory conditions - Thiago F. Martins; Hermes R. Luz; João Luiz H. Faccini; Marcelo B. Labruna (Experimental and Applied Acarology, 2017)

Liolaemus lizards (Squamata: Liolaemidae) as hosts for the nymph of Amblyomma parvitarsum (Acari: Ixodidae), with notes on Rickettsia infection - Sebastián Muñoz-Leal; Evelina L. Tarragona; Thiago F. Martins; Claudia M. Martín; Freddy Burgos-Gallardo; Santiago Nava; Marcelo B. Labruna; Daniel González-Acuña (Experimental and Applied Acarology, 2016)

Ecology of a tick-borne spotted fever in southern Brazil - Felipe S. Krawczak; Lina C. Binder; Caroline S. Oliveira; Francisco B. Costa; Jonas Moraes-Filho; Thiago F. Martins; Jonas Sponchiado; Geruza L. Melo; Fábio Gregori; Gina Polo; Stefan V. Oliveira; Marcelo B. Labruna (Experimental and Applied Acarology, 2016)

Ticks infesting bats (Mammalia: Chiroptera) in the Brazilian Pantanal - Sebastián Muñoz-Leal; Alan Eriksson; Carolina Ferreira Santos; Erich Fischer; Juliana Cardoso de Almeida; Hermes R. Luz; Marcelo B. Labruna (Experimental and Applied Acarology, 2016)

Ticks (Acari: Ixodidae) identified from prey–predator interactions via faecal analysis of Brazilian wild carnivores - Thiago F. Martins; Thaís R. Diniz-Reis; Gustavo S. Libardi; Alexandre R. Percequillo; Luciano M. Verdade; Eliana R. Matushima; Marcelo B. Labruna (Experimental and Applied Acarology, 2015)

Association patterns of ticks (Acari: Ixodida: Ixodidae, Argasidae) of small mammals in Cerrado fragments, western Brazil - Jonas Sponchiado; Geruza L. Melo; Thiago F. Martins; Felipe S. Krawczak; Marcelo B. Labruna; Nilton C. Cáceres (Experimental and Applied Acarology, 2015)

Ticks and rickettsial infection in the wildlife of two regions of the Brazilian Amazon - Herbert S. Soares; Amália R. M. Barbieri; Thiago F. Martins; Antonio H. H. Minervino; Júlia T. R. de Lima; Arlei Marcili; Solange M. Gennari; Marcelo B. Labruna (Experimental and Applied Acarology, 2015)

Investigation of blood parasites of pygoscelid penguins at the King George and Elephant Islands, South Shetlands Archipelago, Antarctica - Ralph Eric Thijl Vanstreels; Flavia R. Miranda; Valeria Ruoppolo; Ana Olívia de Almeida Reis; Erli Schneider Costa; Adriana Rodrigues de Lira Pessôa; João Paulo Machado Torres; Larissa Schmauder Teixeira da Cunha; Roberta da Cruz Piuco; Victor Hugo Valiati; Daniel González-Acuña; Marcelo B. Labruna; et al. (Polar Biology, 2014)

New tick records from the state of Rondônia, western Amazon, Brazil - Thiago F. Martins; José M. Venzal; Flávio A. Terassini; Francisco B. Costa; Arlei Marcili; Luis M. A. Camargo; Darci M. Barros-Battesti; Marcelo B. Labruna (Experimental and Applied Acarology, 2014)

Ornithodoros peropteryx (Acari: Argasidae) in Bolivia: an argasid tick with a single nymphal stage - José M. Venzal; Santiago Nava; Flavio A. Terassini; Maria Ogrzewalska; Luis Marcelo A. Camargo; Marcelo B. Labruna (Experimental and Applied Acarology, 2013)

Description of larva of Amblyomma romitii (Acari: Ixodidae) by optical and scanning electron microscopy, including porotaxy and phylogenetic analysis - Darci M. Barros-Battesti; Diego G. Ramirez; Janio dos Santos Sampaio; Katia M. Famadas; João Luiz H. Faccini; Pablo Henrique Nunes; Thiago F. Martins; Maria Ogrzewalska; Marcelo B. Labruna; Arlei Marcili; Fabio da Silva Barbieri (Experimental and Applied Acarology, 2013)

Ticks (Acari: Ixodidae) associated with small terrestrial mammals in the state of Minas Gerais, southeastern Brazil - Danilo G. Saraiva; Gislene F. S. R. Fournier; Thiago F. Martins; Karla P. G. Leal; Flávia N. Vieira; Edeltrudes M. V. C. Câmara; Claudia G. Costa; Valéria C. Onofrio; Darci M. Barros-Battesti; Alberto A. Guglielmone; Marcelo B. Labruna (Experimental and Applied Acarology, 2012)

Life-cycle and host preference of Amblyomma ovale (Acari: Ixodidae) under laboratory conditions - Thiago F. Martins; Maxwell M. Moura; Marcelo B. Labruna (Experimental and Applied Acarology, 2012)

Morphological and molecular analysis of Ornithonyssus spp. (Acari: Macronyssidae) from small terrestrial mammals in Brazil - Fernanda A. Nieri-Bastos; Marcelo B. Labruna; Arlei Marcili; Lance A. Durden; Leonardo Mendoza-Uribe; Darci M. Barros-Battesti (Experimental and Applied Acarology, 2011)

Cross-mating experiments with geographically different populations of Amblyomma cajennense (Acari: Ixodidae) - Marcelo B. Labruna; João F. Soares; Thiago F. Martins; Herbert S. Soares; Ricardo R. Cabrera (Experimental and Applied Acarology, 2011)

An integrated database on ticks and tick-borne zoonoses in the tropics and subtropics with special reference to developing and emerging countries - Umberto Vesco; Nataša Knap; Marcelo B. Labruna; Tatjana Avšič-Županc; Agustín Estrada-Peña; Alberto A. Guglielmone; Gervasio H. Bechara; Arona Gueye; Andras Lakos; Anna Grindatto; Valeria Conte; Daniele De Meneghi (Experimental and Applied Acarology, 2011)

Hosts, distribution and genetic divergence (16S rDNA) of Amblyomma dubitatum (Acari: Ixodidae) - Santiago Nava; José M. Venzal; Marcelo B. Labruna; Mariano Mastropaolo; Enrique M. González; Atilio J. Mangold; Alberto A. Guglielmone (Experimental and Applied Acarology, 2010)

The life cycle of Amblyomma auricularium (Acari: Ixodidae) using rabbits (Oryctolagus cuniculus) as experimental host - João Luiz H. Faccini; Ana Cristina B. Cardoso; Valeria C. Onofrio; Marcelo B. Labruna; Darci M. Barros-Battesti (Experimental and Applied Acarology, 2010)

Redescription of the female, description of the male, and several new records of Amblyomma parkeri (Acari: Ixodidae), a South American tick species - Marcelo B. Labruna; Valeria C. Onofrio; Lorenza Beati; Márcia Arzua; Patricia B. Bertola; Alberto F. Ribeiro; Darci M. Barros-Battesti (Experimental and Applied Acarology, 2009)

Biology and life cycle of Amblyomma incisum (Acari: Ixodidae) - Matias Pablo J. Szabó; Lucas de F. Pereira; Márcio B. Castro; Marcos V. Garcia; Gustavo S. Sanches; Marcelo B. Labruna (Experimental and Applied Acarology, 2009)

Experimental infection of the rabbit tick, Haemaphysalis leporispalustris, with the bacterium Rickettsia rickettsii, and comparative biology of infected and uninfected tick lineages - Luciana Helena T. Freitas; João Luiz H. Faccini; Marcelo B. Labruna (Experimental and Applied Acarology, 2009)

The effect of temperature and fasting period on the viability of free-living females of Rhipicephalus sanguineus (Acari: Ixodidae) under laboratory conditions - Eliane M. Piranda; Paulo Henrique D. Cançado; Vanessa A. Raia; Tatiane K. de Almeida; Marcelo B. Labruna; João Luiz H. Faccini (Experimental and Applied Acarology, 2008)

Biological aspects of Amblyomma brasiliense (Acari: Ixodidae) under laboratory conditions - Gustavo S. Sanches; Gervásio H. Bechara; Marcos V. Garcia; Marcelo B. Labruna; Matias P. J. Szabó (Experimental and Applied Acarology, 2008)

Ticks collected on birds in the state of São Paulo, Brazil - Marcelo B. Labruna; Luiz F. Sanfilippo; Cristiane Demetrio; Ana C. Menezes; Adriano Pinter; Alberto A. Guglielmone; Luis F. Silveira (Experimental and Applied Acarology, 2007)

Validation and redescription of Amblyomma romitii Tonelli-Rondelli, 1939 (Acari: Ixodidae) - Darci M. Barros-Battesti; Márcia Arzua; Valeria C. Onofrio; Marcelo B. Labruna (Systematic Parasitology, 2007)

Description of the immature stages and redescription of the female of Ixodes schulzei Aragão & Fonseca, 1951 (Acari: Ixodidae), an endemic tick species of Brazil - Darci M. Barros-Battesti; Valeria C. Onofrio; João L. H. Faccini; Marcelo B. Labruna; Ana D. Arruda-Santos; Flávia G. Giacomin (Systematic Parasitology, 2007)

Detection of a novel spotted fever group rickettsia in Amblyomma parvum ticks (Acari: Ixodidae) from Argentina - Richard C. Pacheco; Jonas Moraes-Filho; Santiago Nava; Paulo E. Brandão; Leonardo J. Richtzenhain; Marcelo B. Labruna (Experimental and Applied Acarology, 2007)

Topographical and numerical study of the idiosomal integumentary structures of the larva of four Neotropical species of Amblyomma Koch, 1844 (Acari: Ixodidae) - Fábio S. Barbieri; Samuel C. Chacón; Marcelo B. Labruna; Darci M. Barros-Battesti; João L. H. Faccini; Kátia M. Famadas (Systematic Parasitology, 2007)

Ticks (Acari: Ixodidae) parasitizing humans in an Atlantic rainforest reserve of Southeastern Brazil with notes on host suitability - Matias P. J. Szabó; Marcelo B. Labruna; Karina C. Castagnolli; Marcos V. Garcia; Adriano Pinter; Viviane A. Veronez; Geórgia M. Magalhães; Márcio B. Castro; Alexandre Vogliotti (Experimental and Applied Acarology, 2006)

Redescription of Amblyomma fuscum Neumann, 1907 (Acari: Ixodidae), a rare South America tick confirmed in Brazil - Darci M. Barros-Battesti; Valeria C. Onofrio; Marcelo B. Labruna; João R. Martins; Alberto A. Guglielmone (Systematic Parasitology, 2005)

Ticks (Acari: Ixodida) on wild carnivores in Brazil - Marcelo B. Labruna; Rodrigo S. P. Jorge; Dênis A. Sana; Anah Tereza A. Jácomo; Cyntia K. Kashivakura; Mariana M. Furtado; Claudia Ferro; Samuel A. Perez; Leandro Silveira; Tarcísio S. Santos JR; Samuel R. Marques; Ronaldo G. Morato; et al. (Experimental and Applied Acarology, 2005)

Life cycle of Amblyomma cooperi (Acari: Ixodidae) using capybaras (Hydrochaeris hydrochaeris) as hosts - Marcelo B. Labruna; Adriano Pinter; Rodrigo H.F. Teixeira (Experimental and Applied Acarology, 2004)

Life cycle and host specificity of Amblyomma triste (Acari: Ixodidae) under laboratory conditions - Marcelo B. Labruna; Eric Y.M. Fugisaki; Adriano Pinter; José Maurício B. Duarte; Matias J.P. Szabó (Experimental and Applied Acarology, 2003)

Life-cycle and host specificity of Amblyomma tigrinum (Acari: Ixodidae) under laboratory conditions - Marcelo B. Labruna; Silvio L.P. Souza; Ana C. Menezes; Maurício C. Horta; Adriano Pinter; Solange M. Gennari (Experimental and Applied Acarology, 2002)